Effects of Furrow Corn Straw Mulch on Soil Erosion and Organic Carbon Loss in Sloping Farmland in the Black Soil Region - Haiou Shen; Hongli Li; Hang Liu; Jialong Wu; Chunli Li; Yushi Liang (Agronomy)
Black soil with high fertility is a valuable soil resource, which plays an important role in guaranteeing regional food security and ecological security. Straw return is also a widely recognized way of straw resource utilization. However, it is still not clear which corn straw return method is more suitable for the Chinese black soil region with cold characteristics. The objectives of this study were to classify rainfall patterns (I—light rain with long duration, II—heavy rain with short duration, III—moderate rain with moderate duration; T1 and T2—special rains) and reveal the effects of furrow corn straw mulch—a new straw return—on soil erosion and organic carbon loss. Natural runoff plots (a planned size of 100 m2 and dimensions of 20 m × 5 m for each one) with or without the furrow corn straw mulch, which had slope gradients of 3°, 6° and 9°, were applied for natural rainfalls. Runoff and sediment samples were collected after each erosive rainfall to measure runoff, sediment, and organic carbon concentration. The results showed that when comparing treatments with the furrow corn straw mulch to control treatments, runoff coefficients, sediment concentration, and mean ratios of organic carbon loss in sediment to total carbon loss decreased by 48.0–97.7%, 45.6–99.7%, and 4.7–12.9%, respectively. Furthermore, the ratios of <0.053 mm sediment increased but the ratios of >0.25 mm sediment generally decreased. The mean organic carbon concentration both in runoff and sediment decreased in the following order: II > III > I > T1 > T2. Rainfall pattern II induced greater ratios of organic carbon loss. Therefore, the furrow corn straw mulch measure, which effectively decreased soil erosion and regulated organic carbon loss from the black soil, is suitable for the farmlands in the black soil regions.